HUBUNGAN ANTARA PAPARAN BENZENA DENGAN PROFIL DARAH PADA PEKERJA DI INDUSTRI PERCETAKAN X KOTA SEMARANG - Wahida Inayatun Nikmah; Yusniar Hanani Darundiati; Budiyono Budiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Benzene is one of toxic air pollutants. In printing industry, benzene contained in the ink and solvent. Environmental Protection Agency (EPA) has classified benzene in the Group A (carcinogen for humans). Chronic effect of benzene exposure were defect in bone marrow which characterized by changes in blood profile. The purpose of this research was to analyze the correlation between benzene exposure and blood profile on workers in the printing industry X. The research type was an analytic observational with cross sectional approach. Blood profile includes haemoglobin, erythrocytes, leukocytes, platelets, haematocrit, mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC). Samples were 14 workers in production department printing industry X. About 2-3 cc venous blood of each workers was taken for blood profile analysis. Inhaled benzene by workers taken by using personal dust sampler and carbon active coconut shell charcoal in accordance NIOSH 1501 method. Data were analyzed by univariate and bivariate using Spearman rank correlation test. The result showed that the average inhaled benzene concentration = 0.1322 ppm. The average of haemoglobin = 14.85 gr/dL; erythrocytes = 5.31x106cells/µL; leukocytes = 6.8486x103 cells/µL; platelets = 265.7857x103cells/µL; haematocrit = 43.5143%; MCV = 82.6286 fL; MCH = 28.2 pg, and MCHC = 34.1143 gr/dL. There was a significant correlation between benzene exposure and mean corpuscular volume (MCV) (p=0.005; r=0.705). There were no significant correlation between benzene exposure and haemoglobin, erythrocytes, leukocytes, platelets, haematocrit, MCH and MCHC (p>0.05). The conclusion of this study is inhaled benzene concentration in workers was above REL NIOSH, 0.1 ppm, but that was still in low level exposure. The worker's blood profile still in the normal standard. Benzene exposure correlated to MCV.